A immunosensor for the diagnosis of canine distemper virus infection using SPR and EIS - Basso, Caroline Rodrigues [UNESP]; De Camargo Tozato, Claudia [UNESP]; Mendes Ribeiro, Marcela Cristina [UNESP]; Araujo Junior, João Pessoa [UNESP]; Pedrosa, Valber A. [UNESP] (Royal Society of Chemistry (RSC), 2013)
Canine distemper virus (CDV) is a viral disease that affects dogs and many other carnivores. Clinical diagnosis of CDV is difficult due to the broad spectrum of signs that may be confounded with other respiratory and enteric diseases of dogs. Laboratory analysis is required to diagnose suspected cases. In this study, surface plasmon resonance (SPR) and electrochemical impedance spectroscopy (EIS) methodologies were developed for the detection of canine distemper virus simultaneously. The assay exhibited high specificity, as all the negative controls were not mistakenly detected. The CDV concentration was determined from successive injections into the apparatus, with a linear range from 1.1 to 116.0 ng mL-1. The system exhibited good reproducibility with 4.5% variation between runs after regeneration of the coated surface with a solution of 0.1 M glycine-HCL (pH 3.0). The capacitance and resistance values of the modified interface were calculated from EIS data using an equivalent circuit. It was possible to measure CDV in highly concentrated viruses with good specificity and reproducibility. © 2013 The Royal Society of Chemistry.
Keywords: Canine distemper virus; Clinical diagnosis; High specificity; Laboratory analysis; Modified interfaces; Negative control; Reproducibilities; Resistance values; Amino acids; Electrochemical impedance spectroscopy; Surface plasmon resonance; Viruses; Diagnosis